2013
DOI: 10.1213/ane.0b013e31829e4028
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Use in Fasted Rats Under Sevoflurane Anesthesia and Propofol Anesthesia

Abstract: Sevoflurane anesthesia attenuates glucose-induced insulin secretion without affecting basic insulin secretion, while propofol anesthesia enhances insulin secretion. Propofol anesthesia exaggerates insulin-resistive conditions, whereas sevoflurane anesthesia dose not impair insulin sensitivity; there may be a possible association of TNF-α with insulin-resistive conditions under propofol anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Changes in blood glucose levels during insulin tolerance tests in groups S-ITT, SL-ITT, and P-ITT adenosine triphosphate-sensitive potassium channels in β-islet cells (2)(3)(4)(5). We previously found that propofol anesthesia enhances insulin secretion in rats (6,7). Groups SL-IVGTT and P-IVGTT showed significantly higher plasma insulin levels during IVGTT than group S-IVGTT.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Changes in blood glucose levels during insulin tolerance tests in groups S-ITT, SL-ITT, and P-ITT adenosine triphosphate-sensitive potassium channels in β-islet cells (2)(3)(4)(5). We previously found that propofol anesthesia enhances insulin secretion in rats (6,7). Groups SL-IVGTT and P-IVGTT showed significantly higher plasma insulin levels during IVGTT than group S-IVGTT.…”
Section: Discussionmentioning
confidence: 93%
“…The administered doses of sevoflurane and propofol for maintenance of anesthesia were selected based on our previous protocols (1,6,7). Twenty-one rats were assigned to groups S-IVGTT, SL-IVGTT, and P-IVGTT (n = 7 in each group; Figure 1).…”
Section: Intravenous Glucose Tolerance Test (Ivgtt)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some anaesthetics lower heart rate and blood flow, which may influence nutrient homeostasis. Whilst, several anaesthetic regimens such as pentobarbital and fentanyl-ketamine-midazolam have been shown to have little effect on either blood glucose or insulin release (Guarino et al 2013, Zuurbier et al 2014, other anaesthetics can cause insulin resistance and hyperglycaemia in both mice and rats (Pomplun et al 2004, Brown et al 2005, Tanaka et al 2009, Guarino et al 2013, Sato et al 2013, which could potentially confound interpretation of experimental data generated using anaesthetised animals. For example isofluorane anaesthesia results in significantly suppressed plasma insulin levels, whilst ketamine-medetomidine-atropine anaesthesia results in almost complete suppression of insulin release and hyperglycaemia (Zuurbier et al 2014).…”
Section: Stress and Anaesthesiamentioning
confidence: 99%